A study to estimate the occurrence of peripheral neuropathy among asymptomatic type 2 diabetic patients - S., Nagaraja B.; J., Manjula (International Journal of Advances in Medicine, 2020)
Background: Diabetes is a life long illness characterized by increased blood glucose levels. According to International Diabetes Federation, the number of diabetes already reached 451 million in 2017 and estimated that in 2045, 693 million people will have diabetes. Approximately, 27% of the direct medical cost of diabetes may be attributed to DPN. The objectives of the current study were to estimate the occurrence of peripheral neuropathy among asymptomatic type 2 diabetic patients. The data gained from this study can aid health care providers and primary care providers to understand the occurrence of diabetic peripheral neuropathy in asymptomatic type 2 diabetic patients. Methods: Study was conducted on patients diagnosed with Type 2 Diabetes in hospitals attached to BMCRI .It is a Cross sectional Correlational study done from February 2019 to June 2019. 88 patients who consented for the study and diagnosed with T2DM for at least a period of 5 year were included. Recently diagnosed T2DM, T1DM, pregnant female, patients on chemotherapeutic agents, known case Peripheral neuropathy of any other cause and patients not willing to participate in the study were excluded. Results: Total 57(64.77%) males and 31(35.22%) females with mean 41.12±15 years. Patients relevant history related to of diabetic peripheral neuropathy collected and Michigan peripheral neuropathy screening instrument (MNSI) assessment done using monofilament testing and vibrotherm (table 3). It was noted that 26.13% (23) patients had objective signs of peripheral neuropathy, 17.04% were males, and female (9.09%) and p value were statistically significant <0.001. Conclusions: Our study concluded that, 26.13% occurrence of Peripheral neuropathy in asymptomatic patients with duration of T2DM >5 years. The neuropathy was independently associated with age and duration of symptoms of diabetes prior to the diagnosis.